Application of the INR proton LINAC for development of methods of radiotherapy and nuclear medicine - Akulinichev, S.V.; Aseev, V.N.; Vasiliev, V.N.; Gavrilov, Yu.K.; Grachev, M.I.; Derzhiev, V.I.; Kokoncev, A.A.; Kokoncev, D.A.; Lazebnik, D.B.; Ponomareva, E.V.; Skorkin, V.M.; Yakovlev, I.A. (Вопросы атомной науки и техники, 2013)
The review of the results of researches in the field of proton therapy and contact radiotherapy (high-dose-rate brachytherapy) is presented. Medical beam formation elements for a wide range of proton energies were calculated, elaborated and tested with proton beams. These therapeutic beams cover most sizes and localizations of tumors. Researches of a new source for high-dose-rate brachytherapy with Yb-169 were carried out. This source has several important advantages compared to conventional sources. Experiments of activation of the new source at the INR Neutron complex were performed and therapeutic properties of the new source were confirmed. We also present in this paper the current status of the new target assembly for producing of some PET isotopes with 20 MeV protons. Проведено огляд результатів досліджень в області протонної терапії та контактної радіотерапії (високо-дозової брахітерапії). На підставі розрахунків були виготовлені і випробувані на протонному пучку елемен-ти системи формування базових терапевтичних пучків КПТ ІЯД РАН в широкому діапазоні енергій протонів. Ці пучки дозволяють проводити протонну терапію для новоутворень практично будь-якої локалізації. Були проведені дослідження нового джерела для високодозової брахітерапії на основі ізотопу Yb-169, що має ряд принципових переваг порівняно з іншими джерелами. Проводилися експерименти з активації нового джерела на нейтронному комплексі ІЯД РАН, які підтвердили його терапевтичні властивості. Показано стан справ зі збирання мішені для напрацювання ПЕТ ізотопів на пучку протонів з енергією 20 МеВ. Проведен обзор результатов исследований в области протонной терапии и контактной радиотерапии (высокодозовой брахитерапии). На основании расчетов были изготовлены и испытаны на протонном пучке элементы системы формирования базовых терапевтических пучков КПТ ИЯИ РАН в широком диапазоне энергий протонов. Эти пучки позволяют проводить протонную терапию для новообразований практически любой локализации. Были проведены исследования нового источника для высокодозовой брахитерапии на основе изотопа Yb-169, имеющего ряд принципиальных преимуществ по сравнению с другими источниками. Проводились эксперименты по активации нового источника на нейтронном комплексе ИЯИ РАН, подтвердившие его терапевтические свойства. Показано состояние дел по сборке мишени для наработки ПЭТ изотопов на пучке протонов с энергией 20 МэВ.